Association between global longitudinal strain and myocardial fibrosis biomarkers in patients with end-stage chronic kidney disease. (3rd October 2022) - Ureche, C; Dodi, G; Tapoi, L; Ailoaei, S; Nedelcu, A; Sascau, R; Statescu, C; Covic, A
Abstract: Introduction: Myocardial fibrosis represents a landmark characteristic of uremic cardiomyopathy, leading to a high burden of arrhythmias, diastolic dysfunction (DD) and ultimately heart failure in this population. Collagen-derived biomarkers (Procollagen type I carboxy-terminal propeptide (PICP), Procollagen type III N-terminal peptide (P3NP)) and Galectin-3 (Gal-3) are associated with the extent of myocardial fibrosis on myocardial biopsy. Global longitudinal strain (GLS) as assessed by two-dimensional speckle tracking echocardiography (2D-STE) has been shown to detect subclinical myocardial dysfunction in various populations. The correlation between GLS and the serum level of these biomarkers has not been studied so far. Purpose: The aim of this study was to evaluate the association between the left ventricular GLS measured by 2D-STE and the serum level of three biomarkers (PICP, P3NP, Gal-3) known to be associated with the presence of myocardial fibrosis, in patients with end-stage renal disease (ESRD), not on dialysis. Methods: We conducted a cross-sectional study that included 135 patients with an eGFR (CKD-EPI) <15 ml/min/1.73 m 2, stable, asymptomatic, not on dialysis. We performed a complete transthoracic echocardiography with 2D-STE and determined serum levels of PICP, P3NP and Gal-3 by ELISA. Patients in atrial fibrillation, with a permanent pacemaker or with a poor acoustic window were excluded. Results: The mean age was 59.2±15.5 (median 61 years), 44% of the patients were males, 33% were diabetic, 11% had a history of myocardial infarction and 14% were smokers. The average volumetric ejection fraction (EF) was 54.4±9.8% (median 55%), with only 6.3% of the patients having an EF <40%. The majority of the patients (86.6%) had at least grade I DD, with only 5.3% having a restrictive pattern (grade III DD). The mean GLS was −16.8% ± 0.1 (median −17%). The average serum levels of PICP, P3NP and Gal-3 were 440.2±139.6, 244.9±380.1 and 10.8±6.7, respectively. After regression analysis, GLS was correlated with PICP, P3NP and Gal-3 levels (p=0.005, r=0.88; p=0.001, r=0.75; and p=0.006, r=0.81 respectively). Additionally, GLS was inversely correlated with the severity of DD (p=0.0001, r=0.84). In multiple regression analysis of a model consisting of GLS, PICP, P3NP and Gal-3, the serum level of PICP counted for 34% of the variance of GLS (R2=0.559, p=0.002, F=32.39). Conclusions: In conclusion, this study proves that although stable and asymptomatic, patients with ESRD have lower values of GLS, a high proportion of DD and higher values of PICP, P3NP and Gal-3, when compared with the general population, in spite of a normal EF. Our study is the first to demonstrate that these biomarkers correlated with GLS in patients with ESRD, suggesting that GLS could represent an important tool for estimating the amount of fibrosis and risk stratification in this population. Funding Acknowledgement: Type of funding sources: None.